2018
DOI: 10.2147/cia.s148334
|View full text |Cite
|
Sign up to set email alerts
|

Sources and directions of social support and life satisfaction among solitary Chinese older adults in Hong Kong: the mediating role of sense of loneliness

Abstract: Based on survey data collected from 151 community-dwelling solitary Chinese older adults in Hong Kong, the present study used path analysis to examine the mediating role of sense of loneliness in the relationship between different sources and directions of social support and life satisfaction. The results showed that sense of loneliness mediated the effects of support from families, friends, and support for others on life satisfaction. In addition, a formal source of social support was not associated with life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
49
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 48 publications
3
49
0
4
Order By: Relevance
“…In this paper, ‘healthy family functioning’ is defined as effective interactions and positive relationships within the family (Byles, Byrne, Boyle, & Offord, ). A recent study confirmed that family support can reduce older adults’ sense of loneliness and enhance their life satisfaction (Bai, Yang, & Knapp, ). Similarly, stronger intergenerational relationships reportedly predict greater longevity, fewer depression symptoms, less loneliness, and greater life satisfaction (Hazer, Öztürk, & Gürsoy, ; Lowenstein, ; Bai, ).…”
Section: Introductionmentioning
confidence: 81%
“…In this paper, ‘healthy family functioning’ is defined as effective interactions and positive relationships within the family (Byles, Byrne, Boyle, & Offord, ). A recent study confirmed that family support can reduce older adults’ sense of loneliness and enhance their life satisfaction (Bai, Yang, & Knapp, ). Similarly, stronger intergenerational relationships reportedly predict greater longevity, fewer depression symptoms, less loneliness, and greater life satisfaction (Hazer, Öztürk, & Gürsoy, ; Lowenstein, ; Bai, ).…”
Section: Introductionmentioning
confidence: 81%
“…The older generation tend to be more affected by the various facets of intergenerational interaction namely living arrangement, emotional support in the form of communication and financial support than the younger generation [9][10][11]. In the past, the elderly relied mostly on their children especially in terms of emotional and financial support as they aged and were incapable of solely supporting themselves [12,13]. In the advent of social welfare policies such as medical insurance and pension benefits, the level of dependency on children is likely to reduce.…”
Section: Introductionmentioning
confidence: 99%
“…In general, social support or social resources are necessary to lead a happy and healthy life. Social support is an important component of older adults' happiness and health [6,7,8,9]. Among the sources of social support, the family is considered as the most important factor that influences older adults' happiness [3,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Social support is an important component of older adults' happiness and health [6,7,8,9]. Among the sources of social support, the family is considered as the most important factor that influences older adults' happiness [3,6,7,8,9,10]. The previous studies report the important influence of contextual factors on associations between living arrangements and the happiness [3,8], between living arrangements and health status [3,10] of older individuals.…”
Section: Introductionmentioning
confidence: 99%